Megaproyectos de infraestructura territorial frente a la vulnerabilidad urbana regional-subregional. El caso del departamento de Antioquia (2019)
The main objective of this paper is to address the impact of mega infrastructure projects on the planning and management of the territory in accordance with its vulnerability. As a methodology, it describes, from the point of view of social transaction costs, the infrastructure, order and territorial planning, which allow to orientate the components that are required so that the mega-projects cohere the diffuse conditions derived from the physical space of the territory. As main contributions, the management of mega-projects from the point of view of territorial ordering, planning and ecological dependence, must pass to the scenario of the applied and masterly chair, through the research and proposal foundation as a line of work.